MODELING AND ANALYSIS OF THE ELEMENTS AND STRUCTURE OF THE ARMCHAIR FOR A REST - Genchev, Jancho; Vukov, Georgi; Slavov, Valentin (Innovation in Woodworking Industry and Engineering design, 2013)
Upholstered furniture consists of supporting structure (skeleton) and upholstery. The proposed work presents modeling and analysis of the elements and structure of an armchair for a rest. The study is done on the base of modern software products, using traditional research of this type of sizes and load schemes According to the study, some necessary recommendations for the design optimizing concerning its practical implementation with specific parameters are given